Factors affecting commencement and cessation of smoking behaviour in Malaysian adults - Ghani, W.M.; Razak, I.A.; Yang, Y.H.; Talib, N.A.; Ikeda, N.; Axell, T.; Gupta, P.C.; Handa, Y.; Abdullah, N.; Zain, R.B. (BioMed Central, 2012)
BACKGROUND: Tobacco consumption peak in developed countries has passed, however, it is on the increase in many developing countries. Apart from cigarettes, consumption of local hand-rolled cigarettes such as bidi and rokok daun are prevalent in specific communities. Although factors associated with smoking initiation and cessation has been investigated elsewhere, the only available data for Malaysia is on prevalence. This study aims to investigate factors associated with smoking initiation and cessation which is imperative in designing intervention programs. METHODS: Data were collected from 11,697 adults by trained recording clerks on sociodemographic characteristics, practice of other risk habit and details of smoking such as type, duration and frequency. Smoking commencement and cessation were analyzed using the Kaplan-Meier estimates and log-rank tests. Univariate and multivariate Cox proportional hazard regression models were used to calculate the hazard rate ratios. RESULTS: Males had a much higher prevalence of the habit (61.7%) as compared to females (5.8%). Cessation was found to be most common among the Chinese and those regularly consuming alcoholic beverages. Kaplan-Meier plot shows that although males are more likely to start smoking, females are found to be less likely to stop. History of betel quid chewing and alcohol consumption significantly increase the likelihood of commencement (p < 0.0001), while cessation was least likely among Indians, current quid chewers and kretek users (p < 0.01). CONCLUSIONS: Gender, ethnicity, history of quid chewing and alcohol consumption have been found to be important factors in smoking commencement; while ethnicity, betel quid chewing and type of tobacco smoked influences cessation.